ANALISIS PROSES PENYUSUNAN DAN PELAKSANAAN APBDESA (ANGGARAN PENDAPATAN DAN BELANJA DESA) SECARA AKUNTABEL, TRANSPARAN DAN PARTISIPATIF (STUDI PADA BEBERAPA DESA DI KOTA BANDA ACEH) - Zaini, Ahmad; Ningsih, Endang Surasetyo (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The purpose of this research is to analyze and describe the making and implementation of APBDesa (Anggaran Pendapatan dan Belanja Desa) with accountable, transparent and participation. This research is descriptive research using a qualitative assessment approach. The study population is 89 villages in the town of Banda Aceh by taking 18 sample using purposive sampling method. The data for this study were obtained through interview, documentation and questionnaire-based. The results showed that the overall the process planning and implementation of APBDesa in villages from the research samples already done with accountable, transparent and participation and appropriate with the valid legislation.